2014
DOI: 10.1175/jpo-d-13-064.1
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Layers in the Tropical South Atlantic: Mean Dynamics and Submesoscale Effects*

Abstract: Barrier layers are generated when the surface mixed layer is shallower than the layer where temperature is well mixed, in geographical regions where salinity plays a key role in setting up upper-ocean density stratification. In the tropical oceans, thick barrier layers are also found in a latitude range where spiraling trajectories from surface in situ drifters suggest the presence of predominantly cyclonic submesoscale-like vortices. The authors explore these dynamical processes and their interplay in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
4
15
1
Order By: Relevance
“…The simplest suggestion h = MLD yields zero subduction rate, see equation (27). Such a suggestion is also not in agreement with several studies (Badin et al, 2011;Luneva et al, 2015;McWilliams, 1985;Mensa et al, 2013;Ramachandran et al, 2014;Thomas, 2008;Treguier et al, 1997;Veneziani et al, 2014) that showed that h > MLD implying that below the ML, the flow is still diabatic. The inadequacy of the mixed layer depth to represent the near-isothermal upper layers was also discussed by Gregory (2000, section 2).…”
Section: Extent Of the Sm Regimecontrasting
confidence: 77%
See 2 more Smart Citations
“…The simplest suggestion h = MLD yields zero subduction rate, see equation (27). Such a suggestion is also not in agreement with several studies (Badin et al, 2011;Luneva et al, 2015;McWilliams, 1985;Mensa et al, 2013;Ramachandran et al, 2014;Thomas, 2008;Treguier et al, 1997;Veneziani et al, 2014) that showed that h > MLD implying that below the ML, the flow is still diabatic. The inadequacy of the mixed layer depth to represent the near-isothermal upper layers was also discussed by Gregory (2000, section 2).…”
Section: Extent Of the Sm Regimecontrasting
confidence: 77%
“…Since the results we obtain depend on the underlying instabilities represented by BIs and wind stress, use of an ocean general circulation model (OGCM) to compute the 2‐D velocity trueu¯()z that appears in does not allow us to identify the relative contributions of the two processes to the SM subduction rates. To do so, one needs an analytic treatment in which we take trueu¯()z to be the sum of geostrophic and a‐geostrophic components, trueu¯=ug+uag, where ug=f1zez×Htrueb¯,1emuag=f1ρ1ez0.5em×0.5emzboldτ()z where τ ( z ) is the wind stress and where in the first relation in we have used a constant Htrueb¯ in the mixed layer as suggested by the results of numerical simulations (Mensa et al, ; Veneziani et al, ). We begin with the geostrophic component .…”
Section: Analytic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the SM parameterizations (6)–(9) do not provide a model for h, specifically, its relation with the mixed‐layer depth H. Analytic studies presented below indicate that the sign of tracer fluxes depend on the difference normalhnormalH1, and whether in a given location there is subduction or obduction depends on whether (11) is positive or negative. Previous studies [ McWilliams , ; Mensa et al ., ; Veneziani et al ., ] concluded that h > H, but since they were not specific to the ACC, it may not be legitimate to extrapolate (12) to that region. The model we present in section 5 reproduces relation (12) away from the ACC and shows that in the latter there are three distinct regions characterized by h > H, h = H and h < H (see Figure ).…”
Section: Submesoscale Tracer and Momentum Fluxesmentioning
confidence: 99%
“…To better understand these features, we derive the analytic form of the tracer fluxes. To do so, we take the 2‐D mean velocity trueu¯(z) as the sum of geostrophic and a‐geostrophic (wind‐driven) components trueu¯= ug+uag, ug=f1zez×Htrueb¯, uag=f1ρ1ez×zτ(z), where τ(z) is the wind stress and in the second relation we used the fact that the horizontal buoyancy gradient is constant in the mixed layer [ Mensa et al ., ; Veneziani et al ., ]. Using the second of (13) in (7) and then in (6), we obtain that at z = −H,…”
Section: Submesoscale Tracer and Momentum Fluxesmentioning
confidence: 99%